Rhinitis: adherence to treatment and new technologies. Issue 1 (February 2017) - Braido, Fulvio; Baiardini, Ilaria; Puggioni, Francesca; Garuti, Silvia; Pawankar, Ruby; Walter Canonica, G.
Abstract : Purpose of review: Nonadherence to treatment is a major issue in approximately 50% of patients suffering from chronic diseases. The availability of new technologies could represent a possible way to improve patients' engagement and adherence in a real-life setting. Research and technology tools made available or in process of being made available to patients with allergic diseases and their physicians could potentially improve the management of these disease in daily life by improving adherence. In this review, we sought to outline many of the recent advances in these technological approaches. Recent findings: Short Message Service (SMS) reminder, social networks, wearable devices, mobile applications (Apps), monitoring systems of inhaled device use, often presented as 'serious game' are changing the way of approaching to chronic disease, such as rhinitis, management. Summary: Studies of the role played by various technologies in improving adherence to treatment in rhinitis are still limited as compared with other diseases such as asthma, but the results are encouraging. Further studies in this area may lead to the discovery of novel management approaches that is easy to be integrated in patients' daily life.